Consumers' expectation and liking for cheese: Can familiarity effects resulting from regional differences be highlighted within a country?. (March 2019) - Nacef, Menouar; Lelièvre-Desmas, Maud; Symoneaux, Ronan; Jombart, Laureen; Flahaut, Christophe; Chollet, Sylvie
Highlights: Familiarity with Maroilles cheeses increases liking scores and knowledge. Familiar consumers base their food choice on intrinsic parameters (tasting). Unfamiliar consumers rely on extrinsic parameters (packaging) for food choice. Knowledge influences expectations, but only for familiar consumers. Abstract: Consumers' food choices are affected by various factors whose study is of interest for food industry. This paper aims to investigate the influence of familiarity on the expectation and liking of Maroilles cheese among consumers familiar and unfamiliar with the product in France. It specifically focuses on two elements of the familiarity: consumption frequency and knowledge and studies their interactions. A hedonic test on Maroilles cheeses was carried out with 305 consumers from Lille city (familiar with Maroilles cheese) and from Angers city (unfamiliar). The test included three conditions: blind (tasting without any information), expected (no tasting, presentation of the photo of the packaging) and informed conditions (tasting + presentation of the photo of the packaging). A questionnaire was also administrated to assess their socio-demographic information, theoretical knowledge and consumption habits related to Maroilles cheeses. Results show that, as expected, Lille consumers eat more Maroilles and show higher liking scores for this cheese than Angers consumers do. Lille consumers outperform Angers consumers on their knowledge score and an interaction between the levels of knowledge and exposure is observed: Lille consumers with the higher level of knowledge have higher expectations of Maroilles cheese than Lille consumers with the lower level of knowledge. This effect is not observed with Angers consumers. Moreover, consumers familiar with Maroilles based their hedonic judgment mainly on intrinsic cues (tasting) whereas consumers unfamiliar with Maroilles are more influenced by extrinsic cues (packaging). Familiarity affects how consumers use available information to form product quality judgement.